Social Solidarity and Waria Religiousity: A Netnographic Study of Al-Fatah Islamic Boardingschool Yogyakarta - Muhammad Novan Leany; Ramadhanita Mustika Sari (Lembaga Kajian dan Pemberdayaan Mahasiswa UIN Prof. KH. Saifuddin Zuhri Purwokerto, 2022)
Research on transgender religiosity is interesting to study more deeply. This is because of the public’s view that transgenders are justified as a nuisance or disturbing people’s lives. However, something different happened at the Al-Fatah Islamic Boarding School. Pesantren is used as a place to instill religious values in transgender people. So that it becomes a place for waria to develop religion, or as a place for waria to return to the right path, without the element of coercion. Never view transgenders negatively. The purpose of this study is to get an idea of how the public views transgenders in Al-Fatah Islamic Boarding School and a picture of the growth of transgender religious values in Al-Fatah Islamic Boarding School. This research method uses a descriptive qualitative approach with a virtual netnography approach. Netnography is the process of browsing an entity while using internet processes. This article proves the tips on community solidarity in instilling religious values in transgender women at Al-Fatah Islamic Boarding School there are also other findings, namely the side of tolerance for human characters that are different from other